Students' Problems and Coping Strategies in Writing Undergraduate Theses - Prasetyaningrum, Ari; Suraya, St. Ayu; Fikni, Zahratul; Lailawati, Lailawati; Asrobi, Maman (English Department, Faculty of Education, Universitas Muhammadiyah Jakarta, 2025)
ABSTRACT This study investigates the factors contributing to students' challenges in undergraduate thesis writing within the English Education Study Program at Hamzanwadi University, Nusa Tenggara Barat, Indonesia. It further explores the strategies students employ to overcome these challenges. A mixed-methods approach was adopted, involving 36 eighth-semester students as participants. Data were collected through a close-ended questionnaire and semi-structured interviews to provide quantitative and qualitative insights. The findings indicate that psychological factors were the most significant challenge (78.72%), followed by sociocultural factors (16.51%) and linguistic factors (4.7%). To address these difficulties, students employed coping strategies, including identifying novel research topics and ideas through online books and journals, particularly from recent publications (within five years), and grounding their research in real-world issues. They also reviewed previous undergraduate theses, relevant literature, and methodological texts to strengthen their research framework. Additional measures included attending webinars on research methodology, enhancing internal and external motivation, engaging in intensive discussions with supervisors, and leveraging digital tools such as Grammarly and Quillbot for grammatical refinement and paraphrasing to ensure academic integrity. These findings offer valuable insights into the challenges of thesis writing and highlight practical strategies for students and educators to enhance the thesis-writing experience in higher education.